Quantitative research in communication - Allen, Mike, 1959-; Titsworth, Scott; Hunt, Stephen K.; Sage eBooks (Los Angeles, [Calif.] : SAGE, 2009)
This textbook is designed to be economical and is focused on core topics in quantitative communication research ranging from basic statistical procedures (such as frequency distributions) to more advanced procedures (such as multiple regression).
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Communication -- Statistical methods; Communication -- Data processing; Electronic books